Compassionate Use of Ripretinib for Patients With Metastatic Gastrointestinal Stromal Tumors: Taiwan and Hong Kong Experience - Lin, Li-Ching; Huang, Wen-Kuan; Yen, Chueh-Chuan; Yang, Ching-Yao; Sung, Meng-Ta; Wong, Natalie S. M.; Chua, Daniel T. T.; Lee, Sarah W. M.; Chen, Jen-Shi; Yeh, Chun-Nan (Frontiers in Oncology, 2022)
Background: Ripretinib was recently approved for the fourth-line targeted therapy for advanced gastrointestinal stromal tumor (GIST) refractory to imatinib, sunitinib, and regorafenib based on the pivotal INVICTUS phase III study. The INVICTUS study significantly demonstrated survival benefit of ripretinib in 85 patients with median progression-free survival (PFS) and overall survival (OS) of 6.3 and 15.1 months, respectively. However, treatment outcome of Asian people, including Taiwan and Hong Kong, was lacking. Material and method: A compassionate study regarding ripretinib use for patients with advanced/metastatic GIST was conducted from March 2020 to March 2021 to assess the treatment efficacy and safety in Taiwan and Hong Kong patients. Result: Twenty evaluable patients (16 males and 4 females) with heavily pretreated metastatic GIST receiving ripretinib from March 2020 to March 2021 were enrolled to evaluate the treatment outcome. The response and clinical benefit rate to ripretinib was 25% (5/20) and 60% (12/20), respectively. The median PFS and OS in this compassionate cohort receiving ripretinib were 6.1 months and not reachable, respectively. Albumin less than 3.5 and disease progression after ripretinib use were the two independent unfavorable factors for PFS. There were 14 out of 20 (70%) experiencing any grade adverse event (AE). Loss of hair is the most common grade I to II AE with the incidence of 55%. Grade III AEs included diarrhea, skin rash, and anemia with one patient (5%) for each AE, respectively. Conclusions Late-line ripretinib use in pre-treated Taiwan and Hong Kong patients with advanced GIST showed efficacy consistent with the INVICTUS study. Albumin less than 3.5 and disease progression after ripretinib use were the two independent unfavorable factors for PFS. Ripretinib is generally tolerable with loss of hair being the most common AE.